A novel strategy for enhancing the partial denitrification to treat domestic wastewater by feeding sludge fermentation liquid. (June 2021) - Liu, Xuefan; Wang, Bo; Peng, Yongzhen; Gong, Xiaofei; Gong, Qingteng; Li, Xiyao
Highlights: Sludge fermentation liquid enhanced partial-denitrification in domestic wastewater. The capability of NO3 – -N reduction was enhanced while that of NO2 – -N was weakened. Effluent ratio of NH4 + -N/NO2 – -N is 1:1 which is suitable to couple with anammox. Anammox bacteria was enriched and Ca. Brocadia (0.13%) was detected in phase IV. Abstract: Partial-denitrification (PD; NO3 – →NO2 – ) has recently been proposed to be a feasible choice of NO2 – -N supply for anammox bacteria. In this study, an aerobic/anoxic process for treating domestic wastewater was operated for 176 days to evaluate the feasibility of using sludge fermentation liquid for partial denitrification of the wastewater. Results show that, with the ratio of C/N (COD/ NO3 – -N) increased at anoxic stage, the average NO2 – -N concentration in the effluent and nitrate-to-nitrite transformation ratio (NTR) at anoxic stage showed relative growth. High-throughput sequencing analysis demonstrated that the enhancement of PD can be explained by the increases of Thauera, Paracoccus and Enterobacteriaceae . Moreover, Candidatus_Brocadia (0.13%) was detected as the predominant anammox bacteria. Ex-situ isotopic tracing technique analysis assessed that the ratio of anammox role (ra%) was 7.29%. This study has a great potential for being coupled with the anammox bacteria for advanced nitrogen removal.